EXPERIMENTAL STUDY ON PREDICTIONS OF CYCLING AS AN OPTION FOR URBAN MOBILITY IN INDONESIAN CITIES: A CASE STUDY OF MAKASSAR. - Muhammad Ikram Ulman Idris (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2022)
As one of the nations with high number of populations, Indonesia should concern the best practice and way to design their cities’ urban form and mobility lanes. Covid 19 pandemic has changed many aspects of human activities. During the pandemic, the number of bicycles sold increased more than 1.000 percent. The situation could be a momentum for Indonesians which highly known so depends on motorized vehicle as the main option for mobility, even on a short distance trip. This study aims to inspect the changing of behaviour of Indonesians related to cycling during pandemic and its future. By spreading the questionnaire on earlier stage of the pandemic, and a brief comparison of heatmap on cycling activities, this research revealed that Makassar potentially could provide cycling lanes equally on its land, with almost half of the respondents reveals that they probably choosing cycling as their vehicle to accessing office/services. Key Words : Cycling transport, urban form, cycling lanes, main road, mobility.